Pembinaan Usaha Bordir Kerancang Bukittinggi (Kasus Pada KUB Anggrek dan KUB Jam Gadang) - Gustina, Afifah, Yosi Suryani (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2015)
Kerancang embroidery business is a small business which mostly done by people inBukitinggi. The purpose of this activity is to provide guidance to Kerancang embroiderybusinesses, including human resource development through capacity building ofmanagement attempt to generate better production and clean by using a painting techniquethrough flour singkuit and improve the ability of business in terms of media, using theinternet to generate design are more varied, interesting and high value. The method used isin the form of training, discussion, question and answer session and bring the perpetratorsembroidered practitioners who have proven to be good and acceptable to the market. Thisactivity proved to be very beneficial for a business partner in improving the ability toproduce better products and can compete in the market. Through this activity, theproblems faced by business partners can be resolved so that will increase productivity,which in turn will improve the economy of the small business members.Key word: Kerancang embroidery, business partner, training, practitioners